Impact of spinal cord stimulation on sick leave and disability pension in patients with chronic neuropathic pain: a real-world evidence study in Sweden. Issue 3 (15th March 2023) - Söreskog, Emma; Jacobson, Trolle; Kirketeig, Terje; Fritzell, Peter; Karlsten, Rolf; Zethraeus, Niklas; Borgström, Fredrik
Abstract : Supplemental Digital Content is Available in the Text. Spinal cord stimulation treatment in Sweden decreases disability days and consequently indirect costs. Effect of SCS seemed to have little association with patient characteristics. Abstract: Current research indicates that spinal cord stimulation (SCS) has a positive short-term impact on outcomes, such as quality of life, pain, and productivity in patients with chronic neuropathic pain. However, there is a need for studies on larger population samples. This study used data from Swedish national registers to analyze change and predictors of sick leave and disability pension 2 years before and after SCS treatment. Patients with SCS implanted between 2006 and 2017, and a reference group consisting of 5 individuals matched to each SCS patient without replacement with respect to age, sex, and region of residence, were included. A difference-in-difference approach was used to compare the average change (2 years after treatment vs 2 years before treatment) in net disability days and indirect cost related to disability days for the SCS group, compared with the average change for the reference group. The results showed that SCS treatment in Sweden is associated with a decrease of 21 disability days and consequent decrease in indirect cost of €4127 in working age patients. Large work loss prior to index date was also demonstrated (average 214 days before 1 year), indicating a significant burden on the patient, employers, and the society at large. The number of disability days varied considerably depending on age, sex, socioeconomic variables, and comorbidities; however, the effect of SCS seemed to have little association with patient characteristics. This economic benefit needs to be considered, as well as the clinical outcome, when evaluating the full societal value of SCS.